The 3M Game (Throwing, Catching, and Kicking) the Ball to Develop Kinesthetic Intelligence in Children Aged 4-6 Years - Yulianah, Neneng; Yudha, Rivo Panji (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2024)
This study aims to analyze the influence of 3M games (throwing, catching, and kicking the ball) on the development of kinesthetic intelligence in children aged 5-6 years at RA Senyum Muslim, Bekasi Regency. This type of research focuses on the 3M game (throwing, catching, and kicking the ball) to develop kinesthetic intelligence in children aged 4-6 years at RA Senyum Muslim, Bekasi Regency, using a pre-experimental research method with a Pretest-Posttest design. The population in this study consisted of all children aged 4-6 years at RA Senyum Muslim, Bekasi Regency, totaling 30 students. The sampling technique used in this study was total sampling, meaning all children aged 4-6 years at RA Senyum Muslim, Bekasi Regency, totaling 30 students, were included in the sample. A hypothesis test was then conducted using a paired sample t-test, calculating the magnitude of the effect, and investigating whether the 3M game (throwing, catching, and kicking the ball) had an effect on the kinesthetic intelligence of children aged 4-6 years. The study results explained that the Pre-Test score showed an average kinesthetic intelligence of children (Mean) of 11.20. As for the Post-Test score, the average value of the children's kinesthetic intelligence was 23.97. Since the average value of children's kinesthetic intelligence in the Pre-Test was 11.20, which is lower than the Post-Test score of 23.97, it indicates that descriptively, there is a difference in the average kinesthetic intelligence of children aged 4-6 years. The hypothesis test revealed that the Sig. (2-tailed) value was 0.000 0.05, thus rejecting H0 and accepting Ha. Therefore, it can be concluded that there is a significant difference in the average kinesthetic intelligence of children aged 4-6 years between the Pre-Test and Post-Test at RA Senyum Muslim, Bekasi Regency.